2006
DOI: 10.1002/anie.200603136
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Method To Characterize Framework Aluminum in Aluminosilicates

Abstract: Aluminum sites in zeolites are difficult to locate experimentally, and hence an indirect theoretical approach is proposed that identifies the most likely positions of the aluminum atoms by matching simulation results with available experimental data. The picture shows a model unit cell of FER‐type zeolite with the four distinct T‐sites for aluminum in green.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 34 publications
3
50
0
Order By: Relevance
“…The adsorption isotherms in both structures overlap. The original force field does not perform as well as in the reference 54 , as the calculated adsorption in FAU-type zeolites depends on the specific location of alumina atoms in the zeolite 21 , which is not provided in the reference data. The force field developed in this work provides a lower water adsorption in hydrophylic zeolites than the force field of Fuchs et al, resulting in a worse description of water adsorption in the FAU zeolite, but an excellent agreement with the LTA4A water isotherms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption isotherms in both structures overlap. The original force field does not perform as well as in the reference 54 , as the calculated adsorption in FAU-type zeolites depends on the specific location of alumina atoms in the zeolite 21 , which is not provided in the reference data. The force field developed in this work provides a lower water adsorption in hydrophylic zeolites than the force field of Fuchs et al, resulting in a worse description of water adsorption in the FAU zeolite, but an excellent agreement with the LTA4A water isotherms.…”
Section: Resultsmentioning
confidence: 99%
“…Although some research groups have used a determined force field to study adsorption in different hydrophilic zeolites 19,20 , it is not clear if these force fields can reproduce the adsorption isotherms for different zeolites at different conditions. It has been shown that the adsorption calculated by molecular simulation in zeolites with non framework cations depends on the specific location of the alumina atoms in the structure 21 , which is usually unknown. In the case of the LTA4A zeolite, which has a Si/Al ratio equal to one, the location of the non-framework cations is well known.…”
Section: Introductionmentioning
confidence: 99%
“…This suggestion in ref 206 was followed up by Liu and co-workers. 122,123,207 Liu et al showed that, with the united-atom force field of Dubbeldam et al, 94,97 which uses a σ CH 2 O ) 3.58 Å, an excellent agreement with the experimental data could be obtained. Interestingly, this agreement could only be obtained if the model included the effect of the acid sites in FER.…”
Section: Other Zeolitesmentioning
confidence: 89%
“…The results support the assumption that the difference between the free energy of formation of different hydrocarbons in the same zeolite is almost unaffected by the exact location-and even the presence-of acid sites; that is, freeenergy differences depend almost exclusively on zeolite topology. All computations of free energies of formation are based on free-energy differences between the molecule that is formed and a reference molecule, so simulations aimed at determining free-energy differences can use all-silica structures as excellent approximations of acid zeolites and thus avoid the complex problem 33 of having to account for the exact location-or at least the distribution-of acid sites.…”
Section: Simplification To Successmentioning
confidence: 99%